Comparative study between follicular unit transplantation with intact and non-intact hair bulb in treatment for stable vitiligo. (17th February 2022) - Chen, Yuchong; Yan, Jianna; Chen, Xuewen; Gan, Leimeng; Song, Min; Wang, Jue; Shen, Hongxia; Luo, Hao; Jiang, Long; Luo, Xi; Chen, Xiaogang; Tang, Yichen
Abstract: Objective: To compare the cosmetic efficacy of the transplantation of follicles with intact and non-intact hair bulbs in the treatment for vitiligo. Methods: The single-hair follicle units with intact hair bulbs and un-intact hair bulbs were transplanted into the skin of vitiligo. The diameters of regrowing hair shafts and repigmentation of implanted follicles were detected analyzed by dermatoscopy (Beining BN-PFMF Skin and Hair Visualizer). Results: The survival rates of follicles with intact and non-intact hair bulbs were 60.00% and 50.62%, respectively. The average diameters of hair shafts and repigmentation of the two groups were 92.83 ± 7.26 µm vs 55.86 ± 2.64 µm ( p  < .05), 2.62 ± 0.13 mm vs 2.63 ± 0.17 mm ( p  > .05), respectively. Conclusion: Single follicle transplantation was an alternative effective choice for the treatment of vitiligo. The skin implanted with follicle with non-intact hair bulb was less hairy.